Is the legacy of Max Weber relevant today? (On the centenary of his death) - Titarenko, Larissa G. (Journal of the Belarusian State University. Sociology, 2020)
The article discusses the main issues of the scientific heritage of the classic of world sociology Max Weber, and discusses the reasons why his legacy remains relevant today. It touches upon the problems and difficulties associated with the translation of Weber’s works from German, which led to the inaccuracies in the interpretation of his ideas. The article emphasized the main achievement of Weber that is the creation of an interpretive sociology and its conceptual apparatus. Much attention is paid to the concept of «freedom from values» in connection with Weber’s interpretation of science as a sphere in which there is no place for any criteria other than scientific ones, and the difference between the sphere of science and the sphere of politics, where the individual can openly show his interests and preferences. The methodological relevance of the problems and concepts disclosed by Weber, in particular, the concepts of «ideal type», «types of domination», «charisma», «social action», rationality», «bureaucracy» is considered.
Keywords: Max Weber; interpretive sociology; scientific legacy; charisma; ideal type; social action; rationality